Treatment of maple syrup urine disease with high flow hemodialysis in a neonate - Fatih Aygün; Ertuğrul Kıykım; Çiğdem Aktuğlu-Zeybek; Tanyel Zubarioğlu; Halit Cam (The Turkish Journal of Pediatrics)
Continious renal replacement therapy (CRRT) is a well recognizied treatment of choice in acute renal failure, however CRRT became a preferred treatment of metabolic emergencies with high leucine and ammonia levels like Maple syrup urine disease (MSUD). MSUD is a rare metabolic disorder caused by deficiency in the activity of the branched-chain a-ketoacid dehydrogenase complex. The toxic accumulation of branched chain amino acids during acute metabolic decompensation is associated with the appearance of permanent neurological symptoms. Four patients were admitted to our pediatric intensive care department with complains of poor feeding, vomitting, irratibility and coma. Physical examination of the neonates were similar having stupor, hypotonia and depressed newborn reflexes. The leucine levels were between 930-4400 μmol/L. The diagnosis of MSUD was confirmed in all four. They were treated successfully with high flow CRRT having the rates were between 4120 ml/h/1.73m2 and 9830 ml/h/1.73m2. Early treatment is essential to prevent neurotoxicity and death. CRRT is a choice of treatment in metabolic crisis of MSUD. Herein, we report the successful treatment of acute metabolic decompensation of MSUD with CRRT in 4 neonates.